2008
DOI: 10.1111/j.1525-142x.2008.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid shape divergences between natural and introduced populations of a horned beetle partly mirror divergences between species

Abstract: Onthophagus taurus is a polyphenic beetle in which males express alternative major (horned) and minor (hornless) morphologies largely dependent on larval nutrition. O. taurus was originally limited to a Turanic-European-Mediterranean distribution, but became introduced to several exotic regions in the late 1960s. Using geometric morphometrics, we investigate the present-day morphological shape differentiation patterns among native (Italian) and introduced (Western Australian and Eastern US) populations. We the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Several studies have also begun to investigate genital divergence within and between species of onthophagine beetles. Pizzo et al [11] found significant differences in paramere shape among recently diverged natural and exotic populations of O. taurus , and these divergences were qualitatively similar to those detected when the same species was compared to its sister species, O. illyricus . In contrast, the same study failed to detect corresponding differences in vaginal shape.…”
Section: Introductionmentioning
confidence: 65%
“…Several studies have also begun to investigate genital divergence within and between species of onthophagine beetles. Pizzo et al [11] found significant differences in paramere shape among recently diverged natural and exotic populations of O. taurus , and these divergences were qualitatively similar to those detected when the same species was compared to its sister species, O. illyricus . In contrast, the same study failed to detect corresponding differences in vaginal shape.…”
Section: Introductionmentioning
confidence: 65%
“…Within this framework, the evolution of an exaggerated and complex primary sexual trait may have been an adaptation to avoid hybridization during and after the speciation event. All the above is in keeping with a tenet that assumes reproductive organs evolve quickly in insects (rapid genital evolution), and also with the results of several studies regarding the role of genital divergence in speciation (Dapporto 2010a, b;Gilligan and Wenzel 2008;House and Simmons 2003;Pretorius 2007, Mutanen et al 2007;Parzer and Moczek 2008;Pizzo et al 2008).…”
Section: Interspecific Divergence Between a Obscurus And A Immaturusmentioning
confidence: 83%
“…Discriminant function analysis was carried out on the whole data set of relative warp scores to obtain a classification matrix based on shape variation (in keeping with Janžekovič and Kryštufek 2004;Kryštufek and Janžekovič 2005;Pizzo et al 2006Pizzo et al , 2008 using SPSS v18. We used the percentage of correct classifications of cross-validation to further evaluate interspecific differences in shape (in cross-validation, each case is classified by the functions derived from all cases other than the case in question).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…All specimens were digitized with three replicates in order to reduce the measurement error [9] and these were aligned by using a Generalized Procrustes Analysis (GPA) to superimpose the landmark configurations with least-squares estimates for translation and rotation parameters [10], thus they removed the non-shape effects of translation, rotation, and scale [11]. Each set of analysis under consideration was conducted separately for males and females.…”
Section: B Acquisition Of Outline Datamentioning
confidence: 99%